Uptake and adverse reactions of COVID-19 vaccination among people living with HIV in China: a case–control study. Issue 12 (2nd December 2021) - Zhao, Heping; Wang, Hui; Li, Hui; Zheng, Weiran; Yuan, Tanwei; Feng, Anping; Luo, Dan; Hu, Yuqing; Sun, Yinghui; Lin, Yi-Fan; Zhou, Yiguo; Luo, Ganfeng; et al.
ABSTRACT: Objectives: The coronavirus disease-2019 (COVID-19) pandemic continues to ravage the world. People living with HIV (PLHIV) are one of the most vulnerable groups. This study aims to identify the factors associated with the uptake and adverse reactions of COVID-19 vaccination. Methods: We recruited PLHIV in China by convenience sampling between 7 and 23 February 2021. Participants were asked to complete an online questionnaire. Chi-squared test and multivariable logistic regression were used to assess factors associated with vaccine uptake. Results: A total of 527 vaccinated and 1091 unvaccinated PLHIV were recruited. Individuals who had a higher education, engaged in occupations with a higher risk of COVID-19 infection, received influenza or pneumonia vaccine in the past 3 years (5.40, 3.36–8.77), believed in the effectiveness of vaccines (3.01, 2.20–4.12), and received media information regarding COVID-19 vaccine (2.23, 1.61–3.11), were more likely to be vaccinated. Concerning about adverse reactions (0.31, 0.22–0.44), negative impact on the progression of HIV/AIDS (0.36, 0.26–0.50) or antiretroviral therapy (ART) (0.61, 0.44–0.85), disclosure of HIV infection status (0.69, 0.49–0.96), comorbidities (0.33, 0.22–0.47), being unmarried (0.43, 0.28–0.66) and older age were negatively associated with vaccination. Of the 527 vaccinated PLHIV, 155 (29.4%) PLHIV reported adverse reactions, with pain at the injection site being the most common (18.2%). Conclusions: PLHIV, who are concerned about adverse reactions, negative impact on ART outcome and disclosure of HIV infection status, were less likely to adopt COVID-19 vaccination. To increase vaccination coverage among PLHIV, health-care professionals should emphasize the benefits and necessity of vaccination and provide consultancy regarding adverse reactions.